PERANCANGAN SISTEM DETEKSI PLAT KENDARAAN BERMOTOR MENGGUNAKAN OPENCV BERBASIS WEB - Efendi, Irvan; Elbert Hutabri (Computer Science and Industrial Engineering, 2024)
This research aims to design a motor vehicle license plate detection system using web-based OpenCV, applied in the Sandona residential complex, Batam. This system replaces access cards for entry, enhancing security by automatically detecting registered vehicle license plates. If registered, the gate opens automatically. The methodology includes preliminary studies, literature review, preparation of tools and materials, design, as well as testing and analysis. The system uses NodeMCU ESP8266, a webcam, a servo motor, an ultrasonic sensor, and software developed with Python and OpenCV for image processing. The detection process involves capturing images of license plates, processing the images to extract numbers, and matching them with a database for validation. Testing results show an accuracy rate of 75% under optimal conditions. Accuracy is influenced by the position of the license plate, which must be upright and straight to the camera, as well as adequate lighting conditions. Under ideal conditions, the system works well and can improve access efficiency and security in the Sandona residential complex. Keywords: Computer Vision, Digital Image, NodeMCU ESP8266, Object Detection; Open CV.